The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1262/jrd.45.13
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Reproductive Ultrasonography: A Review

Abstract: Abstract. The advent of ultrasonography over a decade ago has contributed tremendously in the field of bovine reproduction. Ultrasound imaging has shown that cattle exhibit 2 or 3 waves of follicular development during an estrous cycle. Ultrasonography allows monitoring of individual follicles as they grow and/or regress over time and patterns of follicular development can thus be determined with relative precision. Other important applications of ultrasonography in bovine reproduction includes; pregnancy diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
12

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 111 publications
1
27
0
12
Order By: Relevance
“…The peak E 2 and LH concentrations in this study were within the range of those reported previously (Ribadu & Nakao 1999, Saumande & Humbolt 2005. The sequence and time relationships among the various endocrine/ovulation events in this study were also consistent with most of the related data published thus far (Schams et al 1977, Dieleman et al 1986, Larsson 1987, Rajamahendran et al 1989, Stevenson et al 1998, Saumande & Humbolt 2005, but there were some exceptions.…”
Section: Timing Of Estrus Onset E 2 and Lh Peakssupporting
confidence: 92%
“…The peak E 2 and LH concentrations in this study were within the range of those reported previously (Ribadu & Nakao 1999, Saumande & Humbolt 2005. The sequence and time relationships among the various endocrine/ovulation events in this study were also consistent with most of the related data published thus far (Schams et al 1977, Dieleman et al 1986, Larsson 1987, Rajamahendran et al 1989, Stevenson et al 1998, Saumande & Humbolt 2005, but there were some exceptions.…”
Section: Timing Of Estrus Onset E 2 and Lh Peakssupporting
confidence: 92%
“…The linear probes using offer more detailed imaging of examined structures, which predisposes these probes for use in clinical trials (diagnosis of reproductive tract disorders). Moreover, Ribadu and Nakao [1] suggested that in routine bovine reproductive ultrasonography a 5 MHz linear rectal probe is the most effective.…”
Section: Disscusionmentioning
confidence: 99%
“…In veterinary practice, ultrasonography (USG) is the most profound technological advance to study changes in the ovarian morphology, including the characterization of bovine follicular waves and corpus luteum (CL) development during the estrous cycle and pregnancy [1] . The ultrasonographic examination is useful in the diagnosis of ovarian cysts and ovarian tumors in cattle [2] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations